Коммуникационная ось "Юг-Север" в системе внешних связей Армянского нагорья (I тыс. до н. э.) - Зардарян, Мкртич (Зангак-97)
During the development of civilizations of the Armenian Highlands and South Caucasus, the specific geographical location of this region has transformed into a peculiar natural resource, guarantying its participation in different processes – ethnic, cultural, economical, political, social, taking place on both sides of the “Caucasus Shield” – in Near East, as well as on the territory of Eurasian steppes. The long-lasting and multi-vector exchange of material and intellectual values between the traditional groups of partners promoted the formation of certain channels of interregional intercourse. In terms of dependence on the specific natural conditions, as well as cultural-political factors, the system of these channels had a rather stable character, which allows us to consider the dynamics of the exploitation of its concrete branches during considerable periods of time. In the context of problems being observed, the I millennium B.C. draws a special interest, as a period which was marked in the history of the Near Eastern civilizations, and especially of the Armenian Highlands and South Caucasus, by a number of cardinal transformations. The formation and development of the system and structure of interregional cultural and economical exchange takes a special position among the latter. The following article is not oriented towards the presentation of whole spectrum of interactions between the societies and states of Armenian Highlands and South Caucasus with the Near Eastern environment. It is focused upon the analysis of ties of the mentioned region with Mesopotamia and Iran by certain communicational channels.
Keywords: История